2019
DOI: 10.1111/jnc.14901
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine STEPs on synaptic function

Abstract: This is an Editorial Highlight of a manuscript by Mallozzi et al. (2019) in the current issue of the Journal of Neurochemistry, in which the authors detail the biochemical pathway that leads to synaptic depression by cocaine. This pathway requires the adenosine A2A receptor and STEP phosphatases. Activation of the adenosine A2A receptor leads to an increase in intracellular calcium, activation of STEP by dephosphorylation, inhibition of excitatory ionotropic glutamate receptors by dephosphorylation of phospho‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Changes induced in striatal synaptic glutamate transmission were modulated by cocaine (10 µM) by an increase in adenosine levels and the consequent A2AR activation, a mechanism involving the participation of STEP [3] and mediating the A2AR agonist-induced reduction in cocaine self-administration. The possible involvement of A2AR-dopamine (DA) D2R heteroreceptor complex in STEP-mediated A2AR agonist-induced reduction in cocaine self-administration has also be proposed by R. Yasuda in its Editorial [1]. In this heteroreceptor complex, the A2AR protomer allosterically inhibits the DA D2R protomer signaling in the ventral striatal-pallidal GABA neurons [4,5], leading to an inhibition of cocaine self-administration [6][7][8],…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Changes induced in striatal synaptic glutamate transmission were modulated by cocaine (10 µM) by an increase in adenosine levels and the consequent A2AR activation, a mechanism involving the participation of STEP [3] and mediating the A2AR agonist-induced reduction in cocaine self-administration. The possible involvement of A2AR-dopamine (DA) D2R heteroreceptor complex in STEP-mediated A2AR agonist-induced reduction in cocaine self-administration has also be proposed by R. Yasuda in its Editorial [1]. In this heteroreceptor complex, the A2AR protomer allosterically inhibits the DA D2R protomer signaling in the ventral striatal-pallidal GABA neurons [4,5], leading to an inhibition of cocaine self-administration [6][7][8],…”
Section: Introductionmentioning
confidence: 93%
“…The major activation of STEP takes place through activated calcineurin turning on protein phosphatase 1, producing a dephosphorylation of STEP which causes activation of STEP [1]. As to removal of STEP, it was demonstrated that ubiquitination of STEP is produced by synaptic activation causing its degradation.…”
Section: On the Role Of Step A Striatal-enriched Protein Tyrosine Phosphatasementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the involvement of calcineurin suggests the need of intracellular calcium increase. These mechanisms have been very nicely examined and depicted by Robert Yasuda (Yasuda, 2020) who recapitulated the way through which A 2A R modulates cocaine-induced synaptic depression and, possibly, cocaine self-administration, via STEP activation.…”
Section: Evidence Of a Functional Interaction Between A 2a R And Striatal-enriched Protein Tyrosine Phosphatasementioning
confidence: 99%